2011
DOI: 10.4161/psb.6.5.15126
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide production is not required for dihydrosphingosine-induced cell death in tobacco BY-2 cells

Abstract: Sphinganine or dihydrosphingosine (d18:0, DHS), one of the most abundant free sphingoid Long Chain Base (LCB) in plants, is known to induce a calcium-dependent programmed cell death (PCD) in tobacco BY-2 cells. We have recently shown that DHS triggers a production of H 2 O 2 , via the activation of NADPH oxidase(s). However, this production of H 2 O 2 is not correlated with the DHS-induced cell death but would rather be associated with basal cell defense mechanisms. In the present study, we extend our current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Accumulation of GapC in the nucleus was also observed in tobacco BY-2 cells treated with DHS (Testard et al, 2016). DHS is known to trigger an apoptotic-like response in tobacco, and in parallel, to increase ROS and RNS production (Lachaud et al, 2010, 2011; Da Silva et al, 2011). GapC1 accumulation in the nucleus was found to be dependent on NO levels in tobacco cells.…”
Section: Effects Of Redox Modifications Of Glycolytic Fermentative Amentioning
confidence: 99%
“…Accumulation of GapC in the nucleus was also observed in tobacco BY-2 cells treated with DHS (Testard et al, 2016). DHS is known to trigger an apoptotic-like response in tobacco, and in parallel, to increase ROS and RNS production (Lachaud et al, 2010, 2011; Da Silva et al, 2011). GapC1 accumulation in the nucleus was found to be dependent on NO levels in tobacco cells.…”
Section: Effects Of Redox Modifications Of Glycolytic Fermentative Amentioning
confidence: 99%
“…In tobacco BY-2 cells, sphinganine or dihydrosphingosine (d18:0, DHS) induce a calcium dependent PCD and trigger H 2 O 2 production via the activation of NADPH oxidase(s). They also promote NO production, which is required for cell death induction (Da Silva et al, 2011). NO accumulated in Cd-induced PCD and promoted Cd-induced Arabidopsis PCD by promoting MPK6-mediated caspase-3-like activation (Ye et al, 2013).…”
Section: No and Ros In Other Types Of Plant Cell Deathmentioning
confidence: 99%
“…However, some studies have shown that NO is not related to the occurrence of PCD. Da Silva found that NO production in suspension cells of Nicotiana tobacillus was not necessary for PCD induced by hydrospingosine (Da Silva et al, 2011). It can be seen that NO has multiple effects on PCD in plants, which may mainly depend on various factors, such as cell types, cellular redox status, local NO ux and dose and the like (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%